THE EXTENT OF RELIANCE ON PLANNING BUDGETS INMONITORING AND PERFORMANCE EVALUATION: A STUDY IN THE GENERAL COMPANY FOR VEGETABLE OILS (World Economics and Finance Bulletin, 2022)
Management accounting has a fundamental and major role in providing management with information to help it perform its functions, especially planning, control and making sound decisions, as it is the mother system for all accounting information. The extent of the company’s commitment to planning budgets in monitoring and evaluating performance. The researcher came to a set of conclusions, the most important of which was the absence of a department specialized in preparing the planning budgets in the company, as well as the absence of a financial and accounting system that meets the requirements of its preparation. The researcher referred to a set of recommendations, the most important of which was the need for the company’s attention Creating a special section for preparing budgets, as well as providing a financial and accounting system that meets the requirements for preparing planning budgets
Keywords: planning; accounting; monitoring; important